PENINGKATAN VOLUME PENJUALAN MELALUI PELATIHAN MATERI DAN PRAKTIK DIGITAL MARKETING BAGI PARA PELAKU USAHA KECIL MIKRO-PERTANIAN KOTA DEPOK (UKM-P) - Vivi Iswanti Nursyirwan; Sasmita Sari Ardaninggar; Liana Dwi Septiningrum; Dewi Rani Gustiasari; Julian Muhammad Hasan Hasan (S1 Accounting Program, Universitas Pamulang, 2019)
Service to the community conducted by the Lecturer Team of the Faculty of Economics of the University of Pamulang Accounting is conducted by conducting educational training using lecture methods, questions and answers, practices and discussions to micro-small business entrepreneurs about the importance of marketing activities both offline / conventional based, and based online marketing. This program is partnering with micro agriculture micro entrepreneurs in Depok City, especially in Sukmajaya Sub-District, Depok City. The main problem faced by partners is the limited knowledge and skills in marketing agricultural processed products both offline and online. The education program is given with the help of audiovisual infocus media, as well as by providing training in marketing theory based and direct practice of digital based marketing activities by Marketing Lecturers and in collaboration with Digitalpreneur Experts. The main purpose of this community service activity is to provide understanding and knowledge of business actors relating to the power of marketing in the business world. The training was held on 1-3 October 2019, at the Depok City cooperative training center. The evaluation of activities used in community service is an aspect of knowledge and skills. The results of the service activities stated that the training participants got an increase in the aspects of cognition and skills by 27.27% from before the training.